(untitled) (Journal of actual problems of jurisprudence, 2018)
In article positive experience and achievements in regional asthmas of the organization of judicial authority and law- enforcement system of the Republic of Kazakhstan are stated. Carrying out legal reforms is especially noted a role of the Head the State in the organizations also. Key words: Right, the court, the judicial system, the State President.